2014
DOI: 10.2298/pac1402069m
|View full text |Cite
|
Sign up to set email alerts
|

Characterizations of microwave plasma CVD grown polycrystalline diamond coatings for advanced technological applications

Abstract: Polycrystalline diamond (PCD) coatings ranging from few microns to several hundred microns thickness have been grown by 915MHz microwave plasma reactor with 9000W power. The coatings were deposited on 100mm diameter silicon (Si) substrate from few hours to several days of continuous runs. PCD coatings were made freestanding by wet chemical etching technique. The deposited PCDs were evaluated by X-ray diffraction (XRD), scanning electronmicroscopy (SEM), Raman spectroscopy,X-ray photoelectron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Figure 2 b shows the Raman’s map of the FWHM on an area of 100 µm 2 . There is a generally accepted convention that the value of the FWHM greater than 12 cm −1 means a poor quality diamond, and a value lower than 12 cm −1 of a diamond layer is considered good quality [ 16 ]. The Raman spectrum displays also a broad band peaked at 1544 cm −1 corresponding to the non-diamond carbon form with the predominant sp 2 -hybridization.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 2 b shows the Raman’s map of the FWHM on an area of 100 µm 2 . There is a generally accepted convention that the value of the FWHM greater than 12 cm −1 means a poor quality diamond, and a value lower than 12 cm −1 of a diamond layer is considered good quality [ 16 ]. The Raman spectrum displays also a broad band peaked at 1544 cm −1 corresponding to the non-diamond carbon form with the predominant sp 2 -hybridization.…”
Section: Resultsmentioning
confidence: 99%
“…Diamond has the best mechanical properties alongwith high thermal conductivity [81] and very low dielectric loss tangent [82], which make them the only material that can be used as power transmission windows in the gyrotrons used for fusion reactors [25]. Synthetic diamond detector designed for small field dosimetry is used as a dosimeter for synchrotron microbeam and minibeam radiotherapy to ensure highly localised and precise dose delivery [83].…”
Section: Nuclear Engineeringmentioning
confidence: 99%
“…Goyal et al [27] deposited thin (300 nm) nanocrystalline diamond (NCD) films on GaN substrates in Ar/ CH 4 /H 2 mixtures and estimated the TC for NCD to be above that of GaN (130 W m −1 K −1 ), but less than 800 W m −1 K −1 in view of the small (100-200 nm) grain size. Mallik et al [28] reported on a free-standing, translucent PCD film with a TC of 660 W m −1 K −1 ; this relatively low value was due to the poor quality and small thickness (≈80 μm) of the material. A much higher TC of 1800-1900 W m −1 K −1 was reported for free-standing MPCVD PCD disks with diameters and thicknesses up to 119 mm and 2.2 mm, respectively, as manufactured by the Element Six Company [6]; however, no details on the growth process were given.…”
Section: Introductionmentioning
confidence: 99%